(3QjMGfI GdcJGH hJMa GdefJGH aj JQGLe GdCOHGA hGdaUMGA hGdcJGHs - (3CHhYHO Gddg eMeO Hf YHO Gddg Hf SYjO GdSdeGfi GdZQfGWi GdCfOdSj, GdTgjQ HdSGf GdOjf Hf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3CeG HgO MeO Gddg GdPi gjC dedI GdESdGe s
(3BNQgG (B:s
(3ef QSGdI NGWH HgG HYV GdaVdGA (B: (3hbO CYOJfG hGdMeO ddg Jdc GdZhQGI hEf GdfaS dCeGQI hdG Mhd hdG bhI EdG HGddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs